Comparative analysis of antimicrobial resistance pattern and pathogenic characterization of Staphylococcus aureus isolated from hospital effluents wastewater and its adjacent communities in Dhaka city - Mahmud, Hasib; Tushar, Jahid Hasan; Haque, Sanjeda (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.